Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/jdi.12757
|View full text |Cite
|
Sign up to set email alerts
|

High‐volume continuous venovenous hemodiafiltration plus resin hemoperfusion improves severe metformin‐associated toxicity

Abstract: We present the case of a 42‐year‐old female patient who attempted suicide by taking approximately 100 tablets of metformin (500 mg). Laboratory tests revealed severe lactic acidosis with lactate levels of 24 mmol/L and pH of 7.09. The patient was treated with high‐volume continuous venovenous hemodiafiltration (CVVH) and resin‐sorbent hemoperfusion. Metformin concentrations were measured by high‐performance liquid chromatography during CVVH and hemoperfusion treatment. Before extracorporeal treatment, the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Studies originated from North America, in Europe, in Asia, and in multiple countries spanning between 1991 and 2018. In relationship to our defined outcomes, 14 studies reported the outcome of all-cause mortality [ 22 , 25 27 , 29 , 31 , 33 , 37 ], 6 studies reported cardiovascular mortality [ 26 , 27 , 31 , 33 , 37 ], 13 studies reported myocardial ischemia [ 20 , 22 24 , 27 29 , 31 33 , 36 , 37 ], 4 studies reported stroke [ 22 , 31 , 37 ], 5 studies reported hypertension [ 21 , 27 , 30 , 35 ], 5 studies reported peripheral vascular diseases [ 22 , 29 , 31 , 37 ], 4 studies reported heart failure [ 22 , 31 , 37 ], 3 studies reported microvascular events [ 31 , 37 ], 6 studies reported nephropathy [ 21 , 28 , 31 , 34 ], and 2 studies reported oculopathy [ 31 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies originated from North America, in Europe, in Asia, and in multiple countries spanning between 1991 and 2018. In relationship to our defined outcomes, 14 studies reported the outcome of all-cause mortality [ 22 , 25 27 , 29 , 31 , 33 , 37 ], 6 studies reported cardiovascular mortality [ 26 , 27 , 31 , 33 , 37 ], 13 studies reported myocardial ischemia [ 20 , 22 24 , 27 29 , 31 33 , 36 , 37 ], 4 studies reported stroke [ 22 , 31 , 37 ], 5 studies reported hypertension [ 21 , 27 , 30 , 35 ], 5 studies reported peripheral vascular diseases [ 22 , 29 , 31 , 37 ], 4 studies reported heart failure [ 22 , 31 , 37 ], 3 studies reported microvascular events [ 31 , 37 ], 6 studies reported nephropathy [ 21 , 28 , 31 , 34 ], and 2 studies reported oculopathy [ 31 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pooled analysis of 4 studies (n = 2051) [ 22 , 31 , 37 ] reveals that metformin treatment may not reduce the risk of heart failure (RR: 1.02; 95% CI: 0.0.610, 1.71; P = 0.95) versus control, with a low heterogeneity (I 2 = 0, Additional file 1 : Fig S17). There is also no statistical significance for the effect size of stroke (RR: 0.89; 95% CI: 0.53, 1.47; P = 0.64; I 2 = 7.52%, Additional file 1 : Fig S18) [ 22 , 31 , 37 ], hypertension (RR: 1.54; 95% CI: 0.52, 4.61; P = 0.44; I 2 = 35.94%, Additional file 1 : Fig S19) [ 21 , 27 , 30 , 35 ], and peripheral vascular diseases (RR: 0.98; 95% CI: 0.60, 1.60; P = 0.93; I 2 = 0, Additional file 1 : Fig S20) [ 22 , 29 , 31 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…This fact was evidenced in our review, where SLED was used in a few patients (5.4%) for initial RRT. There are a few reports of effective use of resin or charcoal based haem-adsorbent filters in managing patients with severe metformin toxicity[ 43 , 44 ]. However, lack of widespread availability, higher cost, limited data regarding their efficacy and risk of complications especially haemolysis, precludes haemoperfusion (HP) using haemadsorption filters from becoming the modality of choice for ECTR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the discussion above, metformin has a large volume of distribution, so early RRT may be beneficial before the substance distributes throughout the body and tissues [12]. As metformin metabolites cause a severe increase in lactic acid, mortality soars.…”
Section: Discussionmentioning
confidence: 99%